Tumour-Associated Macrophages - Lawrence, Toby.; Hagemann, Thorsten; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Macrophages are tissue resident phagocytes that have important roles in development and immunity. The observation that cancers become infiltrated by large numbers of macrophages was first made by Virchow in 1863, clinical and experimental studies suggest tumor-associated macrophages (TAM) are critical to promote carcinogenesis and tumor-progression, however to this day it still isn’t clear what regulates the recruitment of macrophages in tumors and what drives their pro-tumor functions. This volume will provide an overview of current research on the form and function of TAM, highlighting both the mechanistic roles they play in carcinogenesis and tumor progression as well as the molecular mechanisms that control their phenotype and function, and the final chapter addresses the issue of TAM as a potential target in cancer therapy.
Preface -- Macrophage Phenotype in Tumors -- Role of Tumour-Associated Macrophages in the Regulation of Tumour Angiogenesis -- The Role of Tumor-Associated Macrophages in Malignant Invasion -- Tumor-Induced Immune Suppression by Myeloid Cells -- TAM: A Moving Clinical Target -- Arginine Metanolism and Tumour Associated Macrophages -- Indoleamine 2,3-dioxygenaseAmino acid metabolism and tumor-associated macrophages: regulation in cancer-associated inflammation and immune escape -- Vascular Endothelial Growth Factor and Tumor-associated macrophages -- TLR Signaling and Tumor-associated Macrophages -- SHIP and Tumor-Associated Macrophages -- NF-KappaB-Mediated Regulation of Tumor-Associated Macrophages: Mechanisms and Signifance -- Role of hypoxia-inducible transcription factors HIF-a for TAM function -- Index.        .
Keywords: Cancer research; Pharmacology; Cancer Research; Pharmacology/Toxicology.